1997
DOI: 10.1007/s11745-997-0055-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary arachidonic acid on platelet function, platelet fatty acid composition, and blood coagulation in humans

Abstract: Arachidonic acid (AA) is the precursor of thromboxane and prostacyclin, two of the most active compounds related to platelet function. The effect of dietary AA on platelet function in humans is not understood although a previous study suggested dietary AA might have adverse physiological consequences on platelet function. Here normal healthy male volunteers (n = 10) were fed diets containing 1.7 g/d of AA for 50 d. The control diet contained 210 mg/d of AA. Platelet aggregation in the platelet-rich plasma was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 28 publications
3
51
0
Order By: Relevance
“…18 When healthy volunteers were given Ϸ7 times the usual intake of AA (ie, 1.5 g/d) in a 7-week controlled feeding study, no effects on platelet aggregation, bleeding times, the balance of vasoactive metabolites, serum lipid levels, or immune response were observed. [5][6][7][8] Likewise, in a recent study from Japan, AA supplementation (840 mg/d for 4 weeks) had no effect on any metabolic parameter or platelet function. 19 Consistent with this, in observational studies, higher omega-6 PUFA consumption was associated with unaltered or lower levels of inflammatory markers.…”
Section: Omega-6 Pufas and Inflammationmentioning
confidence: 87%
“…18 When healthy volunteers were given Ϸ7 times the usual intake of AA (ie, 1.5 g/d) in a 7-week controlled feeding study, no effects on platelet aggregation, bleeding times, the balance of vasoactive metabolites, serum lipid levels, or immune response were observed. [5][6][7][8] Likewise, in a recent study from Japan, AA supplementation (840 mg/d for 4 weeks) had no effect on any metabolic parameter or platelet function. 19 Consistent with this, in observational studies, higher omega-6 PUFA consumption was associated with unaltered or lower levels of inflammatory markers.…”
Section: Omega-6 Pufas and Inflammationmentioning
confidence: 87%
“…Nelson and colleagues (23)(24)(25)(26)(27) have studied the effects of dietary supplementation of 4.5 g ARASCO ® /d in humans and found no change in platelet aggregation. Platelet aggregation was not measured in this study, but we found no changes in PT and APTT reflecting normal liver function in producing clotting factors.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fat appears to influence both the atherosclerotic and thrombogenic components of coronary heart disease (CHD) (Miller, 1997;Hornstra, 1980). Previous studies have shown that fatty acids affect coagulation of blood (Leray, 2001;Tholstrup, 2003;Nelson et al, 1997), but the effects of individual fatty acids on haemostasis are still controversial (Hoak, 1997;Knapp, 1997), which depends on both the fatty acid chain length and the degree of saturation (McGregor et al, 1980;Hornstra and Starrenburg, 1973). There is evidence that dietary long-chain saturated fatty acids appear to increase platelet aggregation whereas intake of short and mediumchain fatty acids has been negatively correlated with platelet aggregation (Takachi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%